2017
DOI: 10.15283/ijsc17036
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Human Adipose Derived Stem Cells during Small Molecule Chemical Stimulated Pre-neuronal Differentiation

Abstract: Background: Adipose derived stem cells (ADSCs) are acquired from abdominal liposuction yielding a thousand fold more stem cells per millilitre than those from bone marrow. A large research void exists as to whether ADSCs are capable of transdermal differentiation toward neuronal phenotypes. Previous studies have investigated the use of chemical cocktails with varying inconclusive results. Methods: Human ADSCs were treated with a chemical stimulant, beta-mercaptoethanol, to direct them toward a neuronal-like li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…Furthermore, the dendrite extensions are present in most cells. VPA does not have an influence on the death rate, the cell population has had minimal variation over the treatment time points as opposed to studies with other small chemicals, such as BME and DMSO [2,3,23]. The cell counts and subsequent ALP and Reazurin assays support the stability of the cell culture population with nominal changes over time.…”
Section: Cellular Morphologymentioning
confidence: 77%
See 2 more Smart Citations
“…Furthermore, the dendrite extensions are present in most cells. VPA does not have an influence on the death rate, the cell population has had minimal variation over the treatment time points as opposed to studies with other small chemicals, such as BME and DMSO [2,3,23]. The cell counts and subsequent ALP and Reazurin assays support the stability of the cell culture population with nominal changes over time.…”
Section: Cellular Morphologymentioning
confidence: 77%
“…Bioplex analysis was performed as per Santos et al [3] with 500 ”L aliquots collected at timepoints and controls as follows: DMEM control, starve, B27 control, 0, 3, 6, and 24 h. The assay was performed with Bioplex human 27-plex (M50-0KCAF0Y Bio-Rad Laboratories, Hercules, CA, USA). The data analysis was completed in DanteR software (DanteR version 1.0.0.10.…”
Section: Cytokine and Chemokine Bioplex Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We found that 92% (401 type proteins) of the proteins expressed by ADSCs in humans and mice were consistent. Recently, in a comprehensive protein expression analysis using the iTRAQ measurement method [ 15 ], in which peptide fragments were tagged before performing an analysis similar to LC-MS/MS, it was reported that more than 2000 types of proteins were identified from hADSCs [ 16 ]. In this study, 1653 proteins with one or more peptide fragments was identified in hADSCs, and 1623 were identified in mADSCs.…”
Section: Discussionmentioning
confidence: 99%
“…All samples were centrifuged at 20,000× g for 10 min to remove any cellular debris. Assays were performed according to the manufacturer's instructions, as previously described [62]. Images of results were generated in MS Excel, DanteR (Version 1.0.0.10, Richland, WA, USA) and GraphPad Prism (Version 8.2.1, San Diego, CA, USA).…”
Section: Cytokine Arraymentioning
confidence: 99%